AB0705 INCIDENCE, TREND AND FACTORS ASSOCIATED WITH AMYLOIDOSIS IN PATIENTS WITH SPONDYLOARTHRITIS IN SPAIN. OBSERVATIONAL STUDY BASED ON THE REGISTRATION OF DISCHARGES OF THE GENERAL HOSPITALS OF THE NATIONAL HEALTH SYSTEM (CMBD). (TREND-ESPA STUDY). (2nd June 2020) - Mazzucchelli, R.; Crespí-Villarías, N.; Perez-Fernandez, E.; Almodovar, R.; Quirós, J.; Zarco-Montejo, P.
Abstract : Background: Amyloidosis (AA) is a complication of inflammatory diseases, such as Spondyloarthritis (Spa). It is related to active and long-lasting disease. The treatment of Spa has had a major change in recent years, which has allowed a better control of disease activity. Objectives: Analyze the incidence, trend and factors associated with secondary AA hospitalizations in patients with Spa, in Spain. Methods: Population study based on the analysis of a national administrative database (CMBD) of hospital admissions. Period: 01/01/1999 to 31/12/2015. Study population: patients with diagnosis of Spa who were admitted to any national hospital. Control population: 2 groups have been used as controls: GP: group of the general population (without Spa diagnosis) matched of equal sex, age, year and autonomous community as the study population. RA: all income, in the same period, of patients diagnosed with Rheumatoid Arthritis (RA). Secondary AA admissions were identified by the presence of code 277.3. The trend was analyzed using Generalized Linear Models (MLG). The Odds Ratio (OR) of secondary amyloidosis was calculated in Spa vs GP and Spa vs AR. Results: The database (BD) for analysis consists: 1. Study population: 102, 609 admissions with Spa diagnosis. 2: GP: 102, 609 admissions matched with the study population. 3. - RA: 320.332 admissions. There was a total of 3, 790 admissions with AA diagnosis: 782 (0.79%) at Spa, 74 (0.06%) GP and 2, 924 (0.91%) RA. The main clinical-demographic characteristics patients with Spa and AA versus the rest of Spa are shown in the following table: Conclusion: In Spain, during the period 1999 to 2015, there has been a decrease in the incidence of AA in patients with Spa and Ra. We estimate a decrease of -4.6% per year in Spa and -5.5% per year in Ra. Being male, AS or Spa_EII, and uveitis are associated with AA. Disclosure of Interests: Ramón Mazzucchelli: None declared, Natalia Crespí-Villarías: None declared, Elia Perez-Fernandez: None declared, RAQUEL ALMODOVAR Speakers bureau: Abbvie, Celgene, Janssen, Lilly, Novartis, Pfizer., Javier Quirós: None declared, Pedro Zarco-Montejo Speakers bureau: Abbvie, MSD, Novartis, Pfizer.